ESL TEACHERS’ PERCEPTIONS OF AI-POWERED WRITING ASSISTANTS IN LANGUAGE LEARNING - Thiruchelvan, Thivyah; Zakaria, Nur Yasmin Khairani (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study investigates Malaysian primary school English as a Second Language (ESL) teachers’ perceptions of AI-powered writing assistants, with a focus on the perceived benefits and challenges of using tools such as Grammarly, QuillBot, and ChatGPT. Writing remains a challenging skill for primary pupils, and teachers often face constraints in providing individualized feedback due to large class sizes and varied proficiency levels. AI-powered writing assistants have the potential to address these challenges by providing immediate, personalized feedback and supporting learner autonomy. A quantitative descriptive survey was administered to 100 ESL teachers across five Malaysian states, and data were analyzed using descriptive statistics, including means, standard deviations, frequencies, and percentages. The findings reveal that teachers recognize multiple benefits of AI integration, including enhanced student engagement, improved revision habits, personalized support for weaker pupils, vocabulary development, and promotion of learner independence. However, teachers also identified challenges, such as ethical concerns, overreliance by pupils on AI suggestions, occasional inaccuracies in feedback, insufficient training, and limited digital infrastructure in certain schools. The study highlights the need for targeted professional development, clear ethical guidelines, and equitable access to technology to facilitate responsible and effective AI integration in primary ESL classrooms. By focusing on teachers’ perspectives, this research contributes empirical evidence from a Malaysian primary school context, offering practical and theoretical insights for policymakers, educators, and curriculum planners seeking to enhance writing instruction through AI tools.